The Effect of Corporate Ownership Structure on Corporate Social Responsibility Disclosure Through the Independent Board of Commissioners As a Moderating Variable - Sharon Agnesica Vania Hanaya; Dwi Suhartini (Eduvest - Journal of Universal Studies, 2025)
This research investigates the impact of a company's ownership structure on corporate social responsibility (CSR) disclosure, with the independent board of commissioners acting as a moderating variable. The study provides both theoretical and practical contributions by analyzing how foreign ownership and institutional ownership influence CSR disclosure through the lens of stakeholder theory and agency theory, with the independent board of commissioners as a moderating factor. A quantitative research approach is employed, utilizing secondary data. The study population consists of 30 consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023, resulting in a total of 90 company data points. The sample is selected using purposive sampling. Data analysis is conducted using the Statistical Package for the Social Sciences (SPSS), applying Multiple Linear Regression and Moderated Regression Analysis (MRA). The findings indicate that foreign ownership positively influences CSR disclosure, while institutional ownership also has a positive effect on CSR. However, the independent board of commissioners does not moderate the relationship between foreign ownership and CSR disclosure but does moderate the relationship between institutional ownership and CSR disclosure.